Su Delfino Insolera - Corsani, Gabriele (Ri-Vista. Research for landscape architecture, 2015)
Passeggiata geomorfologica (Geomorphologic Walk) is a short and very attractive text by Delfino Insolera belonging to the noble category of the scientific trip literature. It is intended to combine naturalistic and anthropological aspects. A complex and passionate vision springs from that union, aimed to consider the landscape as a palimpsest of scientific, economic and social aspects contributing to its modelling and transforming. The topic of the Passeggiata geomorfologica concerns the relationship between Bologna and its south side hills, developed as a system linked to the Apennine Mountains and at the same time separated from it by the definite «great rocks precipice». Through that naturalistic accident our hilly system acquires a specific unity, structured as an authentic landscape resource.